A multidisciplinary investigation of Storms Ciara and Dennis, February 2020. (May 2023) - Jardine, Alexander; Selby, Katherine; Higgins, David
Abstract: High magnitude storms have periodically impacted the communities of Western Britain and this storm threat is predicted to increase with climate change. Understanding the factors that contribute to storm catastrophe is essential to mitigate the effects of future storms. This multidisciplinary study collectively analyses meteorological, tidal gauge and newspaper data from Storms Ciara and Dennis in February 2020 to assess the environmental, social and political impacts and causes of the catastrophe in Western Britain. The analysis shows that although the storm period comprising Ciara and Dennis was a meteorological climate anomaly and short-term local authority and community responses were effective, shortcomings in governmental policies likely enhanced storm impacts. The study findings suggest that substantive changes to UK government coastal and fluvial management policies and the wider long-term climate change strategy are required to address climate change risk and reduce community storm vulnerability in Western Britain. The key roles of the media in enhancing public hazard preparedness and raising awareness of the impacts of climate change catastrophes and the wider climate crisis are exhibited. A multidisciplinary mixed methods analysis combining quantitative meteorological and tidal data, qualitative newspaper data and peer-reviewed research is shown to identify the likely cause of catastrophe and can inform future climate change vulnerability mitigation. Highlights: A mixed methods approach is employed to analyse Storms Ciara and Dennis in Western Britain. While statistical anomalies, the storms conform with climate change predictions. Catastrophe occurred despite the best efforts of communities, local authorities and the media. The media plays a key role in improving public hazard preparedness and understanding of climate catastrophes. Further adaptation of UK fluvial and coastal management and wider climate change policy is required.